REGULATORY FRAMEWORK: NAVIGATING ACCOUNTING STANDARDS FOR CRYPTO AND FOREX: https://doi.org/10.5281/zenodo.15527239 - Odilov, Dilshod (Journal of Contemporary World Studies, 2025)
This article examines the evolving regulatory landscape surrounding accounting standards for cryptocurrency and foreign exchange (forex) transactions. As digital currencies and international trading gain momentum, existing financial reporting frameworks struggle to adequately address their complexity and volatility. The study reviews current international accounting standards (e.g., IFRS, GAAP), identifies regulatory gaps, and evaluates guidance provided by standard-setting bodies such as the IASB and FASB. It also highlights best practices for ensuring compliance, consistency, and transparency in crypto and forex accounting. The paper offers policy recommendations for regulators and accounting professionals navigating this dynamic financial environment.